2017
DOI: 10.1371/journal.pone.0176473
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent tuberculosis and associated factors: A five - year countrywide study in Uzbekistan

Abstract: BackgroundIn Uzbekistan, despite stable and relatively high tuberculosis treatment success rates, relatively high rates of recurrent tuberculosis have recently been reported. Recurrent tuberculosis is when a patient who was treated for pulmonary tuberculosis and cured, later develops the disease again. This requires closer analysis to identify possible causes and recommend interventions to improve the situation. Using countrywide data, this study aimed to analyse trends in recurrent tuberculosis cases and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
6
13
1
2
Order By: Relevance
“…We found recurrent TB among patients with age group between 18 to 65 years and we could not find any significant correlation between recurrent TB and patients occupation. Similarly a study by Gadoev et al in 2017 from Uzbekistan have also reported that recurrent TB was not associated with any specific age group and occupation of patients in their study [10].…”
Section: Discussionsupporting
confidence: 57%
“…We found recurrent TB among patients with age group between 18 to 65 years and we could not find any significant correlation between recurrent TB and patients occupation. Similarly a study by Gadoev et al in 2017 from Uzbekistan have also reported that recurrent TB was not associated with any specific age group and occupation of patients in their study [10].…”
Section: Discussionsupporting
confidence: 57%
“…10 Recurrent TB patients also had a higher likelihood of having an unfavorable treatment outcome compared with new TB cases. 11 In this study, male patients were more than female patients. A study by Salim et al in Bangladesh also found male predominance among TB patients.…”
Section: Discussionmentioning
confidence: 62%
“…One of the limitations of the study is the small sample size, leading to the large confidence intervals in our estimates. However, data from similar incidence settings show similar proportions of relapse and reinfection [9,2628], and therefore we do not expect these proportions to change extensively, even if we included a larger sample size.…”
Section: Discussionmentioning
confidence: 99%